Cardiovascular diseases worsen the maternal prognosis of COVID-19 - Testa, Carolina Burgarelli; Godoi, Luciana Graziela de; Bortolotto, Maria Rita de Figueiredo Lemos; Monroy, Nátaly Adriana Jiménez; Mattos, Bruna Rodrigues de; Rodrigues, Agatha Sacramento; Francisco, Rossana Pulcineli Vieira (PLOS ONE, 2023)
Cardiovascular diseases (CVD) are a risk factor for severe cases of COVID-19. There are no studies evaluating whether the presence of CVD in pregnant and postpartum women with COVID-19 is associated with a worse prognosis. In an anonymized open database of the Ministry of Health, we selected cases of pregnant and postpartum women who were hospitalized due to COVID-19 infection and with data regarding their CVD status. In the SIVEP GRIPE data dictionary, CVD is defined as “presence of cardiovascular disease”, excluding those of neurological and nephrological causes that are pointed out in another field. The patients were divided into two groups according to the presence or absence of CVD (CVD and non-CVD groups). Among the 1,876,953 reported cases, 3,562 confirmed cases of pregnant and postpartum women were included, of which 602 had CVD. Patients with CVD had an older age (p<0,001), a higher incidence of diabetes (p<0,001) and obesity (p<0,001), a higher frequency of systemic (p<0,001) and respiratory symptoms (p<0,001). CVD was a risk factor for ICU admission (p<0,001), ventilatory support (p = 0.004) and orotracheal intubation in the third trimester (OR 1.30 CI95%1.04–1.62). The group CVD had a higher mortality (18.9% vs. 13.5%, p<0,001), with a 32% higher risk of death (OR 1.32 CI95%1.16–1.50). Moreover, the risk was increased in the second (OR 1.94 CI95%1.43–2.63) and third (OR 1.29 CI95%1.04–1.60) trimesters, as well as puerperium (OR 1.27 CI95%1.03–1.56). Hospitalized obstetric patients with CVD and COVID-19 are more symptomatic. Their management demand more ICU admission and ventilatory support and the mortality is higher.